Delayering the reference coal price to maximize coal non-tax state revenue - Za'im, Muhammad (WIM Solusi Prima, 2026)
Indonesia is the third largest coal producing country in the world. National coal production has experienced an increasing trend with a growth rate of 5.1% in the last 10 years. Article 33 paragraph (3) of the 1945 Constitution mandates the state to control its natural resources (SDA) and use them to achieve people's prosperity. One of the efforts to embody the mandate of the Constitution is in the form of implementing Non-Tax State Revenue (PNBP). PNBP in the coal sector plays an important role in state revenue. PNBP in the coal sector experienced a significant increase in 2022 but then decreased in recent times, especially after the implementation of the Reference Coal Price (HBA) layering for coal royalty PNBP. The HBA layering policy was identified as causing a PNBP loss of around 18% or IDR 15.56 trillion in 2023. This study concludes that it is necessary to simplify coal royalties in the form of returning the HBA to 1 layer/delayering. This is projected to increase PNBP royalties by 7.62% or around Rp 5.87 trillion. This policy still allows companies to obtain positive NPM. This policy is also able to play a major role in accelerating social welfare through funding various development programs such as making the National Health Insurance (JKN) program free for 9.32 million residents and the Free Nutritious Meal (MBG) program for 546 thousand students.